Intra-aortic balloon counterpulsation timing: A new numerical model for programming and training in the clinical environment. (October 2020) - De Lazzari, Claudio; De Lazzari, Beatrice; Iacovoni, Attilio; Marconi, Silvia; Papa, Silvia; Capoccia, Massimo; Badagliacca, Roberto; Vizza, Carmine Dario
Highlights: The paper "Intra-Aortic Balloon Counterpulsation Timing: A New Numerical Model for Programming and Training in the Clinical Environment.", is original research from our ongoing program on numerical simulation applied to the clinical environment. In this work we present a new numerical model of the intraaortic balloon pump (IABP). The new model also allows us to simulate patient weaning from IABP assistance. Furthermore, the cardiovascular network model in which the IABP is inserted, allows us to simulate also a mechanical ventilatory assistance that is very important in patients affected by COVID-19. Abstract: Background and Objective: The intra-aortic balloon pump (IABP) is the most widely available device for short-term mechanical circulatory support, often used to wean off cardiopulmonary bypass or combined with extra-corporeal membrane oxygenation support or as a bridge to a left ventricular assist device. Although based on a relatively simple principle, its complex interaction with the cardiovascular system remains challenging and open to debate. The aim of this work was focused on the development of a new numerical model of IABP. Methods: The new model was implemented in CARDIOSIM©, which is a modular software simulator of the cardiovascular system used in research and e-learning environment. The IABP is inserted into the systemic bed divided in aortic, thoracic and two abdominal tracts modelled with resistances, inertances and compliances. The effect induced by the balloon is reproduced in each tract of the aorta by the presence of compliances connected to PIABP generator and resistances. PIABP generator reproduces the balloon pressure with the option to change IABP timing. We have used literature data to validate the potential of this new numerical model. Results: The results have shown that our simulations reproduced the typical effects induced during IABP assistance. We have also simulated the effects induced by the device on the hemodynamic variables when the IABP ratio was set to 1:1, 1:2, 1:4 and 1:8. The outcome of these simulations is in accordance with literature data measured in the clinical environment. Conclusions: The new IABP module is easy to manage and can be used as a training tool in a clinical setting. Although based on literature data, the outcome of the simulations is encouraging. Additional work is ongoing with a view to further validate its features. The configuration of CARDIOSIM© presented in this work allows the simulation of the effects induced by mechanical ventilatory assistance. This facility may have significant importance in the management of patients affected by COVID-19 when they require mechanical circulatory support devices.